Empirical scaling relations for pseudo relative velocity spectra in western Himalaya and northeastern India. Issue 106 (March 2018) - Gupta, I.D.; Trifunac, M.D.
Abstract: In this paper, frequency-dependent empirical scaling equations are developed for pseudo relative velocity ( PSV ) spectrum amplitudes of strong earthquake ground accelerations in western Himalaya and northeastern India for five ratios of critical damping ζ = 0.00, 0.02, 0.05, 0.10, and 0.20. These are based on the frequency-dependent attenuation functions developed in our recent work (Gupta and Trifunac[38] ) for these two regions. The proposed scaling relations are shown to have physically realistic dependence on earthquake magnitude, source-to-site distance, and local site geological and soil conditions. The extension of the empirical P S V amplitudes to short and long periods, beyond the empirical period range, is also illustrated using available techniques (Trifunac[89, 90] ). To demonstrate the validity of a long-period extension, independent estimates of peak ground displacement from recorded accelerograms and estimates of the seismic moment from distant recordings of earthquakes are shown to be in good agreement with the extended spectral amplitudes. The validity of a short-period extension has been also tested by comparing the values of pseudo acceleration spectral amplitudes at short periods with the recorded peak ground accelerations. The realistic nature of short- and long-period extensions provides additional tests for the accuracy of the present scaling relationships. Such relationships can thus be considered to provide a sound basis for macro- and micro-zoning specific to the highly seismic regions of western Himalaya and northeastern India. Highlights: Frequency dependent attenuation of strong motion from Himalayan earthquakes. Scaling equations for PSV Spectra from Himalayan sources. Scaling strong motion amplitudes in northern India up to distances of 250 km. Tests of empirical PSV spectra at long periods in terms of seismic moment.